A Burns-Krantz type theorem for domains with corners - ZAITSEV, DMITRI (Springer, 2006)
The goal of this paper is twofold. First, to give purely local boundary uniqueness results for maps defined only on one side as germs at a boundary point and hence not necessarily sending any domain to itself and also under the weaker assumption that $f(z)=z+o(|z-p|^3)$ holds only for $z$ in a proper cone in $D$ with vertex $p$. Such results have no analogues in one complex variable in contrast to the situation when a domain is preserved. And second, to extend the above results from boundaries of domains to submanifolds of higher codimension.
PUBLISHED
Keywords: Pure & Applied Mathematics